Risk of desmoid tumours after open and laparoscopic colectomy in patients with familial adenomatous polyposis. Issue 5 (3rd February 2014) - Vitellaro, M.; Sala, P.; Signoroni, S.; Radice, P.; Fortuzzi, S.; Civelli, E. M.; Ballardini, G.; Kleiman, D. A.; Morrissey, K. P.; Bertario, L.
<x xml:space="preserve">Abstract</x> Background Desmoid tumour (DT) is a main cause of death after prophylactic colectomy in patients with familial adenomatous polyposis (FAP). The purpose of this study was to evaluate the impact of prophylactic laparoscopic colectomy on the risk of developing DT in patients with FAP. Methods The database of a single institution was reviewed. Patients with classical FAP with defined genotype who underwent either open or laparoscopic colectomy between 1947 and 2011 were included in the study. The impact of various demographic and clinical features on the risk of developing DT was assessed. Results A total of 672 patients underwent prophylactic colectomy: 602 by an open and 70 by a laparoscopic approach. With a median (range) follow‐up of 132 (0–516) months in the open group and 60 (12–108) months in the laparoscopic group, 98 patients (16·3 per cent) developed DT after an open procedure compared with three (4 per cent) following laparoscopic surgery. The estimated cumulative risk of developing DT at 5 years after surgery was 13·0 per cent in the open group and 4 per cent in the laparoscopic group (P = 0·042). In multivariable analysis, female sex (hazard ratio (HR) 2·18, 95 per cent confidence interval 1·40 to 3·39), adenomatous polyposis coli mutation distal to codon 1400 (HR 3·85, 1·90 to 7·80), proctocolectomy (HR 1·67, 1·06 to 2·61), open colectomy (HR 6·84, 1·96 to 23·98) and year of surgery (HR 1·04, 1·01 to 1·07) were independent risk factors for the diagnosis of DT after prophylactic surgery. Conclusion Laparoscopic surgery decreased the risk of DT after prophylactic colectomy in patients with FAP.